Using Blockchain-Enabled Solutions as SDG Accelerators in the International Development Space - Ahmet Faruk Aysan (11902115) (2021)
As the world is striving to recover from the shockwaves triggered by the COVID-19 crisis, all hands are needed on deck to transition towards green recovery and make peace with nature as prerequisites of a global sustainable development pathway. In this paper, we examine the blockchain hype, the gaps in the knowledge, and the tools needed to build promising use cases for blockchain technology to accelerate global efforts in this decade of action towards achieving the SDGs. We attempt to break the “hype cycle” portraying blockchain’s superiority by navigating a rational blockchain use case development approach. By prototyping an SDG Acceleration Scorecard to use blockchain-enabled solutions as SDG accelerators, we aim to provide useful insights towards developing an integrated approach that is fit-for-purpose to guide organizations and practitioners in their quest to make informed decisions to design and implement blockchain-backed solutions as SDG accelerators. Acknowledging the limitations in prototyping such tools, we believe these are minimally viable products and should be considered as living tools that can further evolve as the blockchain technology matures, its pace of adoption increases, lessons are learned, and good practices and standards are widely shared and internalized by teams and organizations working on innovation for development. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su13074025